2011
DOI: 10.1177/1932202x11415007
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Engineering Into K-6 Curriculum

Abstract: The fields of gifted and engineering education share many common interests, and their students share many common attributes. Infusing and making engineering implicit in the K-6 education programs creates opportunities to develop concepts, skills, and habits of the mind that are valuable in all disciplines while providing opportunities to discover and develop talent in the science, technology, engineering, and mathematics (STEM) disciplines. SummaryEngineering, the E in science, technology, engineering, and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Given that engineering is also viewed as a content domain accessible to college majors, the implementation of engineering curriculum in the primary grades differentiates by acceleration. In addition, the engineering design process at the center of engineering curricula has been linked to the development of creativity—a goal espoused in the field of gifted education (Mann et al, 2011). Second, the use of biography has a long history as a curricular approach in gifted education (Hollingworth, 1925; Robinson, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that engineering is also viewed as a content domain accessible to college majors, the implementation of engineering curriculum in the primary grades differentiates by acceleration. In addition, the engineering design process at the center of engineering curricula has been linked to the development of creativity—a goal espoused in the field of gifted education (Mann et al, 2011). Second, the use of biography has a long history as a curricular approach in gifted education (Hollingworth, 1925; Robinson, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The arrival of the Next Generation Science standards with their focus on engineering practices has opened a new academic domain once thought the purview of college-age students and practicing professionals; the salience of engineering in the elementary school has increased (Anning, 1994; Cunningham & Carlsen, 2014; Cunningham & Hester, 2007; Miaoulis, 2014). Mann, Mann, Strutz, Duncan, and Yoon (2011) noted the similarities between gifted education and engineering education which share interests in creativity, innovation, problem solving, and the visualization of solutions. More specifically, engineering provides an engaging curricular platform for the development of talents in young, promising learners from low-income households (Robinson, 2017b; Robinson & Kidd, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Considering the characteristics of STEAM-based education, it is expected to positively affect students' career choices, cooperative workings, and STEAM attitudes. General studies conducted with gifted students in the literature (Mann, Mann, Strutz, Duncan & Yoon, 2011;Robinson, Dailey, Hughes & Cotabish, 2014;Sternberg, 2019;Sloan, 2020); studies on STEM careers of gifted students (Kim, Roh & Cho, 2016;Şahin & Yildirim, 2020;Yu & Jen, 2021); studies on talented students' STEM attitudes (Wieselmann, Roehrig & Kim, 2020;Bircan & Köksal, 2020;Ceylan, Ermiş & Yıldız, 2018). However, a limited number of studies (Sağat & Karakuş, 2020) have been encountered in the field of STEAM education in gifted students, and no study has been encountered on the effect of STEAM on cooperative working skills.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…To this end, our educational system must consider how we are preparing our students, especially our advanced learners, to meet these ever increasing and changing needs. Furthermore, Mann, Mann, Strutz, Duncan, and Yoon (2011) stated that engineering is a linking subject and can be used across the curriculum to facilitate active learning among all learners. Mann and colleagues also suggested that EDP provides gifted learners opportunities to engage in challenging tasks through varying the levels of sophistication, breadth, and depth of a subject.…”
Section: Why Focus On Edps?mentioning
confidence: 99%